O fenômeno da violência sob o domínio do capital - Conceição, Clarisse Maria da (2015)
This dissertation consists of a study on the phenomenon of violence within the capitalist relations of production, seeking to understand the production and human social reproduction through a historical and critical perspective. We therefore consider that the material basis of social reproduction, based on the job, leads the dynamics of production and social relations. Therefore, depending on the structure of social production and its form of ownership by men, will be unveiled the incidence and configuration of violence in human society in its most varying degrees. It is our objective to analyze the causal links that put violence as a lever for the accumulation and consolidation of the capital system in the capitalist mode of production and how this problem takes shape and manifests itself in the lives of men from the new organization of the productive forces and social. For this purpose, through a literature review, we take as theoretical basis of Karl Marx's arguments, Friedrich Engels and some authors of Marxist matrix. Thus, we realize that in the presence of the capitalist system conform manifestations of violence overlapped directly on the control strategies of capital over labor, for the purpose of subjecting the zorkers to the capitalist system dictates the play. In this direction, to investigate the material bases of violence from the development of socio-productive relations in the capital of the command, we made an analysis of the causal links expressed in the relationshipcapital, which can put the violence as a mechanism of control of capital over work, impacting directly on the lives of the working class. Thus, the discussion permeates the changes in work organization in the social reproduction process, from the primitive accumulation of capital, which conforms the transition stage of feudalism, until the consolidation of the capitalist mode of production. Finally, we conducted an analysis of new expressions of violence in the organization of work Taylor / Ford and Toyotist in the context of monopoly capitalism, with repercussions in social life, beyond the economic dimension, by the change in the ways of managing the workforce. Intentamos demonstrate that the capitalist relations violence is also present within the labor relations.